2018
DOI: 10.1177/1933719117732156
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Ovarian Function With Human Placenta-Derived Mesenchymal Stem Cells in Autoimmune-Induced Premature Ovarian Failure Mice Mediated by Treg Cells and Associated Cytokines

Abstract: Regulatory T (Treg) cells play a key role in the regulation of autoimmunity and transplantation. Human placenta-derived mesenchymal stem cell (hPMSC) transplantation has a potential to restore ovarian dysfunction associated with premature ovarian failure (POF), while the exact function of the Treg cells in the transplantation still needs to be further investigated. In this study, hPMSCs were intravenously injected into POF mice following zona pellucida glycoprotein 3 (pZP3) treatment. Ovarian function was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 41 publications
1
72
0
2
Order By: Relevance
“…These indicate that hPMSCs transplantation is beneficial for the recovery of ovarian function of POF mice. Previous studies have shown that the hPMSCs transplantation could promote follicular development, and improve the ovarian reserve capacity (Yin et al, ; Zhang et al, ). These are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These indicate that hPMSCs transplantation is beneficial for the recovery of ovarian function of POF mice. Previous studies have shown that the hPMSCs transplantation could promote follicular development, and improve the ovarian reserve capacity (Yin et al, ; Zhang et al, ). These are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…And during pregnancy, the women have been tested negative for human immunodeficiency virus I, hepatitis B, and hepatitis C following informed consent. The hPMSCs were isolated and cultured as previously described (Yin et al, , b). The cell membrane and intracytoplasmic molecular markers of hPMSCs were examined using flow cytometry to confirm the phenotype of hPMSCs as we previously described (Yin et al, , b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that PD-MSCs have therapeutic bene ts in mice with premature ovarian failure because they regulate regulatory T-cell activity and cytokines [18,19].…”
Section: Introductionmentioning
confidence: 99%